2018
DOI: 10.1016/j.neo.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Activated Adipose-Derived Stromal Cells Promote Breast Cancer Growth and Invasion

Abstract: Obese women diagnosed with breast cancer have an increased risk for metastasis, and the underlying mechanisms are not well established. Within the mammary gland, adipose-derived stromal cells (ASCs) are heterogeneous cells with the capacity to differentiate into multiple mesenchymal lineages. To study the effects of obesity on ASCs, mice were fed a control diet (CD) or high-fat diet (HFD) to induce obesity, and ASCs were isolated from the mammary glands of lean and obese mice. We observed that obesity increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 96 publications
4
39
0
Order By: Relevance
“…Leptin, which is secreted by adipocytes and significantly enhanced in obesity, has been shown to promote CSCs [39], potentially through regulation of Notch signaling [40]. Adipocytes may also induce invasive and aggressive tumor cell behavior through secretion of cytokines [25], and we have previously observed that adipose-derived stromal cells isolated from the mammary glands of obese mice enhanced local invasion of Met-1 and EO771 cells through secretion of insulin-like growth factor-1 [41]. Interestingly, isolated tumor cells from obese mice retained the ability to proliferate at a higher rate through multiple passages, which may suggest that obesity induces epigenetic changes within breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, which is secreted by adipocytes and significantly enhanced in obesity, has been shown to promote CSCs [39], potentially through regulation of Notch signaling [40]. Adipocytes may also induce invasive and aggressive tumor cell behavior through secretion of cytokines [25], and we have previously observed that adipose-derived stromal cells isolated from the mammary glands of obese mice enhanced local invasion of Met-1 and EO771 cells through secretion of insulin-like growth factor-1 [41]. Interestingly, isolated tumor cells from obese mice retained the ability to proliferate at a higher rate through multiple passages, which may suggest that obesity induces epigenetic changes within breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the top pathways of the involution ECM-CAFs that were unique of this ECM subgroup, fatty acid metabolism and peroxisome hallmarks, suggested that these cells may correspond to adipocyte-like fibroblasts arisen through a dedifferentiation process of mature adipocytes 38 or transdifferentiation process of activated fibroblasts 39 . Adipocyte-derived fibroblasts secrete fibronectin and collagen I and have invasive properties 38,40 . Moreover, during the stromal remodelling stage in involution, there is a re-differentiation of the adipocytes 31,41 .…”
Section: Cafs From Pymt/elf5 Mammary Tumours Show Features Of Mimicrymentioning
confidence: 99%
“…[127] not shown here). ECM remodeling activated by obesity with its underlying chronic inflammation suggests that obesity or chronic inflammation is not enough as it needs fibrosis, which is subsequently remodeled for aggressive cancer phenotype cells that show enhanced growth and invasiveness [128].…”
Section: Morbid Obesitymentioning
confidence: 99%